A Salute to Juan Pablo Izquierdo - Schidlowsky, León (Revista Musical Chilena, 2013)
This article deals with the musical and personal contacts of Juan Pablo Izquierdo with León Schidlowsky, a Chilean-Israeli composer. These contacts started some fifty years ago when both Izquierdo and Schidlowsky resided in Chile. Hans Loewe, a German-Chilean cellist, was also part of this group. Afterwards they resumed their contact in Israel, where Schidlowsky presently resides, when Izquierdo became musical director of the Testimonium Israel Festival in Jerusalem.